IMPLEMENTASI METODE MD5 UNTUK MENDETEKSI ORISINALITAS FILE AUDIO - Sapria Ulandari Lubis (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2019)
The problem of the originality of the file is about how the file can be maintained its authenticity and ensures that the file has never been changed at all. In this study the object file used is the audio file. The process of manipulating files often occurs during data transmission activities from the sender to the recipient. The solution that can be done to handle the crime of manipulation is to apply a hash type cryptographic technique in which the hash value is encrypted from an audio file that can be used as a keyword to ensure the audio file has never been manipulated or has been manipulated. The hash cryptographic algorithm used is the type of MD5 algorithm. The results obtained from the process of implementing the MD5 algorithm using MATLAB R2010a software and the HASH Pro application are audio file hash codes. Keywords: Implementation, Encryption, Decryption, MD5 Method, Cryptography.